2011
DOI: 10.1016/j.msec.2011.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Wear performance of laser processed tantalum coatings

Abstract: This first generation investigation evaluates the in vitro tribological performance of laser-processed Ta coatings on Ti for load-bearing implant applications. Linear reciprocating wear tests in simulated body fluid showed one order of magnitude less wear rate, of the order of 10−4mm3(N.m)−1, for Ta coatings compared to Ti. Our results demonstrate that Ta coatings can potentially minimize the early-stage bone-implant interface micro-motion induced wear debris generation due to their excellent bioactivity compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Large variation in the hardness can be attributed to the variations in concentration and distribution of MgO particles in the coatings. The high hardness of Ta+MgO coatings compared to Ta coatings can potentially minimize the early-stage bone-implant interface micro-motion induced wear debris generation and associated implant loosening [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Large variation in the hardness can be attributed to the variations in concentration and distribution of MgO particles in the coatings. The high hardness of Ta+MgO coatings compared to Ta coatings can potentially minimize the early-stage bone-implant interface micro-motion induced wear debris generation and associated implant loosening [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Quantification of the cell proliferation using MTT assay showed higher proliferation of cells on the Ta coatings than Ti substrate. Furthermore, wear properties of the LENS™ processed Ta coatings was almost an order of magnitude lower than the Ti substrates [174]. These results can be seen in Fig.…”
Section: Additive Manufacturing (Am) Of Different Biomaterialsmentioning
confidence: 93%
“…The bioactivity of the Ta coatings was thus further amplified by selective doping with MgO, as shown in Fig. 28 [173,174]. Vrancken et al reported the SLM processing of Ti64 alloy composite with 10 wt% Mo additions [176].…”
Section: Additive Manufacturing (Am) Of Different Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations